An Integrated Framework of Online Learning Effectiveness in Institutions of Higher Learning - Mohamad Rohieszan Ramdan, Khoo Yin Yin, Dayang Rafidah Syariff M. Fuad, Azita Yonus @ Ahmad, Suzyanty Mohd Shokory (Tanjung Malim, 2024)
An Integrated Framework of Online Learning Effectiveness in Institutions of Higher Learning by Mohamad Rohieszan Ramdan, Khoo Yin Yin, Dayang Rafidah Syariff M. Fuad, Azita Yonus @ Ahmad, Suzyanty Mohd Shokory